Use of Multiphase CT Protocols in 18 Countries: Appropriateness and Radiation Doses - Rastogi, Shivam; Singh, Ramandeep; Borse, Riddhi; Zujic, Petra Valkovic; Segota, Doris; Diklic, Ana; Jurkovic, Slaven; Ali, Antar; Kharita, Hassan Mohammed; Al-Naemi, Huda M.; Alkalbani, Jokha; Al-Rasbi, Amaal; et al. (SAGE Publications, 2020)
Purpose: To assess the frequency, appropriateness, and radiation doses associated with multiphase computed tomography (CT) protocols for routine chest and abdomen–pelvis examinations in 18 countries. Materials and Methods: In collaboration with the International Atomic Energy Agency, multi-institutional data on clinical indications, number of scan phases, scan parameters, and radiation dose descriptors (CT dose–index volume; dose–length product [DLP]) were collected for routine chest (n = 1706 patients) and abdomen–pelvis (n = 426 patients) CT from 18 institutions in Asia, Africa, and Europe. Two radiologists scored the need for each phase based on clinical indications (1 = not indicated, 2 = probably indicated, 3 = indicated). We surveyed 11 institutions for their practice regarding single-phase and multiphase CT examinations. Data were analyzed with the Student t test. Results: Most institutions use multiphase protocols for routine chest (10/18 institutions) and routine abdomen–pelvis (10/11 institutions that supplied data for abdomen–pelvis) CT examinations. Most institutions (10/11) do not modify scan parameters between different scan phases. Respective total DLP for 1-, 2-, and 3-phase routine chest CT was 272, 518, and 820 mGy·cm, respectively. Corresponding values for 1- to 5-phase routine abdomen–pelvis CT were 400, 726, 1218, 1214, and 1458 mGy cm, respectively. For multiphase CT protocols, there were no differences in scan parameters and radiation doses between different phases for either chest or abdomen–pelvis CT (P = 0.40-0.99). Multiphase CT examinations were unnecessary in 100% of routine chest CT and in 63% of routine abdomen–pelvis CT examinations. Conclusions: Multiphase scan protocols for the routine chest and abdomen–pelvis CT examinations are unnecessary, and their use increases radiation dose.
Keywords: CT chest, CT abdomen–pelvis, multiphase scanning, radiation dose, justification